2007
DOI: 10.1038/modpathol.3800728
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lymph vessel invasion identified by the endothelial lymphatic marker D2-40 in node negative breast cancer

Abstract: Monoclonal antibody D2-40, a marker of lymphatic endothelium, identifies tumor emboli in lymph vessels. The aim of the study was to assess whether D2-40 þ lymph vessel invasion (LVI) correlates with clinicopathologic factors including lymphovascular invasion (LVI) as assessed by haematoxylin and eosin-stained sections (H&E þ or H&EÀ) and to assess the prognostic significance in node-negative breast cancer. The study group consisted of 303 node-negative breast cancer patients that had a median follow-up of 7.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
4
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 38 publications
(66 reference statements)
10
81
4
8
Order By: Relevance
“…[2][3][4][5] Recently, it has been shown that immunostaining, especially with D2-40, may be useful to detect missed H & E LVI. 10,11 In a previous work on lymph node-negative tumors, we also observed that D2-40 increases the diagnostic sensitivity of LVI by a factor of 1.4, and strengthens the prognostic impact of this factor. 9 As only peritumoral LVI has prognostic significance, this analysis cannot be easily performed on tissue microarray blocks.…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4][5] Recently, it has been shown that immunostaining, especially with D2-40, may be useful to detect missed H & E LVI. 10,11 In a previous work on lymph node-negative tumors, we also observed that D2-40 increases the diagnostic sensitivity of LVI by a factor of 1.4, and strengthens the prognostic impact of this factor. 9 As only peritumoral LVI has prognostic significance, this analysis cannot be easily performed on tissue microarray blocks.…”
Section: Discussionmentioning
confidence: 96%
“…For survival analysis, the main end points were distant metastases recurrence, and overall distant metastases-related survival (a previous study on node negative patients showed that lymph vessel invasion was only prognostic for distant metastases 11 ). To determine the probability that patients would remain free of distant metastases, we defined recurrence as any first recurrence at a distant site.…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal antibody D2-40 has often been used as a marker of lymphatic endothelium to identify tumor emboli in lymph vessels. 11 However, D2-40 does not only stain lymph vessels but also breast myopethelial cells (Figure 1). The growth pattern of tumor cells surrounded by D2-40-positive myoepitelial cells generally enables distinction of ductal carcinoma in situ from lymphovascular invasion.…”
mentioning
confidence: 97%
“…Invasion of tumor cells into lymphatic vessels is a critical step in metastasis, and lymph vessel invasion (LVI) is a predictor for axillary lymph node metastasis and a prognostic factor in node-negative cancer [2][3][4][5][6][7][8]. LVI can also be used to determine the appropriate indications for chemotherapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%